Peningkatan Kebugaran Jasmani Melalui Pemberian Olahraga Masyarakat Senam Aerobik Mix pada Masyarakat Dusun Morkolak Barat Desa Kramat Kecamatan Bangkalan - Anintya Sada Rosandi; Andun Sudijandoko (Jurusan Pendidikan Kesehatan dan Rekreasi, 2022)
Background: : The purpose of this study was to socialize and exercise the community and to determine the effect of mixed aerobic exercise on increasing the physical fitness of the people of West Morkolak Hamlet, Kramat Village, Bangkalan District. Methods: This study includes a pre-experiment with One Group Pretest-Posttest Design. The research subjects were 31 people who were given mixed aerobic exercise treatment and their physical fitness was measured before and after being treated with the Multistage Fitness Test. The pre-test and post-test data were analyzed using paired t-test. Results: The results showed that there was a significant effect on the provision of mixed aerobic exercise on the physical fitness of the people of West Morkolak Hamlet, Kramat Village, Bangkalan District (sig <0.05) and an increase in physical fitness from 24.606 to 27.513. Conclusions: So, it can be concluded that mixed aerobic exercise can provide an effective and significant influence on the women of the West Morkolak community, Bangkalan Regency.